ICT Update 74: ICT4Ag - setting the scene - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
ICT Update is a bimonthly printed and on-line magazine (http://ictupdate.cta.int) and an accompanying e-mail newsletter published by CTA. This issue focuses on CTA international conference ICT4Ag.